Comment on “A universally applicable method of calculating confidence bands for ice nucleation spectra derived from droplet freezing experiments” by Fahy et al. (2022) - G. Vali (Atmospheric Measurement Techniques, 2023)
The analysis methods in Fahy et al. (2022) and their interpretation of experiments with water drops containing ice-nucleating particles raise some technical issues and prompt a discussion of the principles involved in the use of differential spectra.